2018
DOI: 10.1177/0733464818779936
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Care Health Care Aides’ Perceptions of Decision-Making Processes in Transferring Residents to Acute Care Services

Abstract: Most transfers of long-term care (LTC) facility residents to the emergency department (ED) via 911 calls are necessary. Avoidable transfers can have adverse effects including increased confusion and dehydration. Around 20% of transfers are perceived to be avoidable or unnecessary, yet decision making around transfers is complex and poorly understood. Using a qualitative-focused ethnographic approach, we examined 20 health care aides’ (HCAs) perceptions of decision processes leading to transfer using e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(49 citation statements)
references
References 43 publications
(54 reference statements)
0
48
0
Order By: Relevance
“…It is worth noting that most studies of loneliness and social isolation and ED visits have focused on community-dwelling older adults and therefore they do not consider the organizational and staffing factors in institutional settings—like SL— that add yet another layer of complexity when considering factors related to ED visits and other health service use [ 41 ]. For example, studies in institutional settings like NH have found that the decision to transfer a resident to ED is influenced by hierarchical reporting structures, perception of staff roles and expertise, and communication processes [ 42 ]. Using information available in administrative health data, we were unable to meaningfully assess how specific organizational factors in SL might influence loneliness, social isolation, and health service use.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that most studies of loneliness and social isolation and ED visits have focused on community-dwelling older adults and therefore they do not consider the organizational and staffing factors in institutional settings—like SL— that add yet another layer of complexity when considering factors related to ED visits and other health service use [ 41 ]. For example, studies in institutional settings like NH have found that the decision to transfer a resident to ED is influenced by hierarchical reporting structures, perception of staff roles and expertise, and communication processes [ 42 ]. Using information available in administrative health data, we were unable to meaningfully assess how specific organizational factors in SL might influence loneliness, social isolation, and health service use.…”
Section: Discussionmentioning
confidence: 99%
“…Despite family involvement not directly influencing death, family involvement was included in this model because research supports that families are often not effectively prepared for end-of-life processes, and family involvement in decisions to transfer have been linked to avoidable transitions (Tate et al, 2020;Trahan et al, 2016). Other studies show resident ED utilization may be more likely upon family request, or when older persons perceive they have low levels of social support (Barken et al, 2016;Dermody et al, 2017;Tate et al, 2020;Trahan et al, 2016). Including this variable in the model provides a preliminary framework for adding other factors related to the interactions between families and health care professionals involved in transition decisions, and advance care planning.…”
Section: Discussionmentioning
confidence: 99%
“…Given the conflicting reports related to the effect of ownership model and resident death (Anic et al, 2014;Menec et al, 2009), research should explore how ownership model related to staffing levels and staff-mix can influence family involvement in resident care to reduce transitions in instances when quality end-of-life care could be provided on site. Research should determine the influence of regional context in future modeling work (e.g., availability and access to diagnostic services, LTC site proximity to hospital, access to or awareness of alternative health services, resident case-mix in facilities (Avdic, 2014;Cornillon et al, 2016;Tate et al, 2020). Further work is needed to include factors related to advance care planning, such as training or availability of specialized clinicians for this purpose and the number and quality of formal conversations with care teams regarding end-of-life care (Wilson et al, 2020;Bollig et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike primary and acute care settings, NHs are not required to engage a resident physician for round-the-clock medical coverage. Hence, most NHs outsource their medical care services for residents to private general practitioners on a contract basis, and registered nurses (RNs), enrolled nurses (ENs), and nursing aides remain the primary healthcare providers Tate et al, 2018 ). Given that physicians are often off-site, NH nurses often play a major role in deciding residents' transfer to the ED during an acute situation or medical emergency .…”
Section: Introductionmentioning
confidence: 99%